The development of ability and satisfaction in learning about pronunciation words diphthongs by using to pronunciation skill in Thai language with lt technique of prathom suksa 4 students. - Waduangsri, Supaporn (Journal for Developing the Social and Community, 2023)
The objectives of this research were 1) to improve the reading aloud of diphthongs by using the visualization skills exercises for Grade 4 students with efficiency according to the criteria 70/70. 2) Compare the scores of diphthongs reading skills. of students during before and after learning with the visualization skill exercises and 3) to study the students' satisfaction with learning with the visualization skills exercises. The target group is Grade 4 students in the second semester of the 2019 academic year in Rattana Bundit Kindergarten Rattanawapi District The research instruments consisted of 1) a practice form on reading aloud diphthongs for grade 4 students. 2) 12 learning management plans on reading aloud diphthongs. 3) a test to measure the skills of reading aloud diphthongs during class, 4) a test to measure the skills of reading skills of diphthongs before and after learning 1 set of Grade 4 students; and 5) a satisfaction questionnaire on the learning with visual skill exercises on reading aloud diphthongs for grade 4 students was a rating scale by using statistics for data analysis, mean, percentage, standard deviation. The effectiveness index and hypothesis testing were performed using t-test (Dependent Sample). The efficiency of the Grade 4 students was 70/70, which was higher than the specified criteria. 2) The Grade 4 students had a statistically significantly higher score on learning achievement after school than before. Level .05 3) The index of effectiveness of the visualization skill exercise on reading aloud diphthongs for Grade 4 students was at the highest level. The reading of diphthongs for grade 4 students was at the highest level ( = 4.36, S.D = 0.45).